E-Wallet for UNITARIANS - Kai, Soh Ze; Azhari, Mohammad Hazim (IT for Society, 2024)
This E-Wallet for UNITARIANS was focused on to user friendly, the platform it’s easy to understand and using it, by browsing menu page, transfer, recharge and pay. Also, it has peer-to-peer features, users can send money directly to one another just using their matric number. In this platform, had a simple checkout flow for user to make payments and transfers, it will make user to do a few steps to complete the transaction.